Development of an Interactive Multimedia Module on Andragogy For Community Education Tutors - Daddy Darmawan; Puji Hadiyanti; Durotul Yatimah; Karta Sasmita; Lei Wanpeng (Journal of Nonformal Education, 2023)
This study explores the concept of community education, emphasizing the role of tutors in facilitating effective learning experiences for adults. Community education empowers individuals by enhancing their knowledge, skills, and awareness of societal issues. Tutors play a crucial role in this process, employing various teaching strategies to engage learners and cater to their needs. However, challenges exist, including tutor qualifications, teaching consistency, and adult learning management. The study introduces the concept of Andragogy, which focuses on empowering adults in their learning journey, considering their real-life circumstances and learning preferences. Andragogy highlights the importance of interactive teaching methods, enjoyable programs, and personalized approaches. The research develops an interactive multimedia Andragogy (MIA) module using the Multimedia Development Life Cycle (MDLC) model. This module aims to enhance community education tutors' teaching capabilities for adult learners. Survey data analysis reveals that the MIA Module significantly improves participants' media literacy comprehension and information access skills. The module's learner-centered approach and interactive design align with educational theories like experiential learning and constructivism, promoting active engagement and critical thinking. Moreover, the module's adaptability and flexible learning strategies resonate with Universal Design for Learning (UDL) principles, ensuring inclusivity. The study highlights the positive impact of the MIA Module on enhancing media literacy and information access skills within the context of community education. The module's design, adaptability, and interactive elements make it relevant and effective in contemporary education.